Performance improvement of solar dryer using an auxiliary heat source under different values of airflow rates - Alkahdery, L. A.; Yurchenko, Alexey V.; Mohammed, J. A.-K; Mekhtiyev, Ali D.; Neshina, Elena G. (Eurasian physical technical journal)
One of the most crucial methods for preserving agricultural produce is solar drying. The major focus of this paper is increasing solar drying systems' effectiveness. The development of new methods and variables that may have an impact on the functionality of solar dryers aids in enhancing their efficiency. An indirect-type solar dryer for drying agricultural products is proposed and developed in this study. A dryer consisting of a solar flat plate air collector, an insulated drying chamber, an auxiliary (electric) heat source, and an electric fan is constructed to improve the dryer's performance. The dryer's most typical function is to blow hot air at the product, forcing the water in it to evaporate. The effect of air temperature and velocity on evaporation rate has been studied experimentally. Tests with three different airflow rates—0.042, 0.0735, and 0.105 m3/s—are conducted. When there is little or no solar radiation, an auxiliary heater is used to provide sufficient heat. For varying airflow rates, solar mode and electrical mode were tested experimentally with only one energy source in each mode. The findings revealed that using a different heat source in addition to solar radiation will allow you to keep the air temperature in the drying chamber between 32oC and 42oC. Also, it was found that for the whole drying process at high air velocities, the temperature had less influence on the dryer's performance.